Reproductive tract infection and treatment seeking behaviour of the married women of reproductive age in a slum of Dhaka City - Sarkar, Mekhala; Akter, Seikh Farid Uddin; Rahman, Md Zillur (Ibrahim Medical College, 2007)
Objectives: To determine the proportion of reproductive tract infection (RTI) among the married women of reproductive age in a slum of Dhaka and to ascertain their treatment seeking behaviour. Materials and Methods: A cross sectional study was carried out among 207 married women of reproductive age (15-49 years). RTI was diagnosed using the ‘modified syndromic approach’ as suggested by the World Health Organization. Data were collected through face-to-face interview by using a semi-structured questionnaire. Place and period of the study: The study was undertaken from March to June in the year 2003 in the Naderkhan slum of Rayer Bazar area in Dhaka City. Results: The proportion of RTI among the study population was 45.4% and abnormal vaginal discharge was the most frequently encountered symptom. Family size and occupation of the respondents as well as of their husbands had shown significant influence on the occurrence of RTI (p<0.05) while other socio-demographic characteristics failed to show any association. Of the 94 women detected with RTI, only 26.6% of them received any treatment for the same. For vaginal discharge, lower abdominal pain and painful coitus, majority of the respondents sought treatment from traditional healers and for difficulties in urination and vaginal itching majority of them received treatment from a chemist. Conclusion: Although a considerable number of the married women of reproductive age living in the slum suffered from various types of RTIs, only one fourth of them received any sort of treatment, and that also mainly from the traditional healers. Bangladesh being a signatory to the MDG, maternal health is a priority area. Urban slums cannot be overlooked.